The role of lead users in new product development in the healthcare sector - Bhebhe, Meluleki (Stellenbosch : Stellenbosch University, 2025)
Bhebhe, M. 2025. The role of lead users in New Product Development in the healthcare sector. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/7a6ba644-f658-4d33-8874-29c7e787cbc3